Lab-Scale Carbonation of Wood Ash for CO2-Sequestration - Koch, Robin; Sailer, Gregor; Paczkowski, Sebastian; Pelz, Stefan; Poetsch, Jens; Müller, Joachim (Energies (Basel), 2021)
This study evaluated the CO2 sequestration potential with combustion ashes in the aqueous phase. The aim was to provide a cost-effective carbon sequestration method for combustion unit operators (flue gas cleaning) or biogas producers (biogas upgrading). Therefore, two separate test series were executed to identify the carbonation efficiency (CE) of bottom wood ash (1) at different mixing ratios with water in batch experiments and (2) under dynamic flow conditions. It was furthermore evaluated whether subsequent use of the carbonated wood ash for soil amendment could be possible and whether the process water could be passed into the sewage. The batch test series showed that different mixing ratios of wood ash and water had an influence on the CE. The flow series showed that the mean CE varied between approximately 14% and 17%. Thus, the ash proved to be suitable for carbonation processes. The process water was dischargeable, and the carbonated wood ash has potential for chalking, as no legal thresholds were exceeded. Therefore, wood ash carbonation could be used as a low-tech CO2 sequestration technology. Compared to existing energy consuming and cost intensive carbon capture and storage technologies, sequestration with ash could be beneficial, as it represents a low-tech approach.